2006
DOI: 10.1021/ja060453p
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Highly Ordered Mesoporous Titania Films Consisting of Crystalline Nanopillars with Inverse Mesospace by Structural Transformation

Abstract: Highly ordered mesoporous titania films consisting of crystalline nanopillars with open-spaced, perpendicular, and continuous porosity have been prepared via structural transformation from a 3D hexagonal mesostructure during the thermal treatment. The mechanism of the structural transformation is explained by the crystallization of the titania framework and the large contraction of the initial 3D hexagonal mesostructured film upon calcination. This structural transformation provides a new approach to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 13 publications
(11 reference statements)
7
141
0
Order By: Relevance
“…[18] This result indicates that the amount of Pluronic P123 (ratio to titanium species) in the precursor solution is mainly important for controlling mesostructure. The concentration of Pluronic P123 hardly influenced formation of the mesostructure, possibly because the solvents (mainly ethanol) were evaporated readily by spin coating.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[18] This result indicates that the amount of Pluronic P123 (ratio to titanium species) in the precursor solution is mainly important for controlling mesostructure. The concentration of Pluronic P123 hardly influenced formation of the mesostructure, possibly because the solvents (mainly ethanol) were evaporated readily by spin coating.…”
Section: Resultsmentioning
confidence: 96%
“…[22] As a special case, regularly arranged nanopillar films seem to be obtained by controlled thermal treatment (e.g., slow heating) for gradual crystallization of titania frameworks. [17,18] The nanopillar structures are interesting for managing porosity of anatase films (sufficient and relatively uniform mesospaces between the nanopillars). Porous films Abstract: A transparent film of threedimensional (3D) hexagonal (P6 3 / mmc) mesostructured titania was fabricated according to a modified procedure using triblock copolymer Pluronic P123.…”
Section: Introductionmentioning
confidence: 99%
“…However, its position is shifted to higher angles in R-MTF-400 and R-MTF-450, indicating the decrease of the interplane distance, which agrees with the above-mentioned film shrinkage. 23,24 The decrease of the peak intensity in these samples is ascribed to the fusion of the cage-like pores into vertical channels decreasing the contrast of the electron density. We also tried 500 o C in the hydrogen treatment of MTF.…”
Section: 22mentioning
confidence: 89%
“…The most convenient method of preparing mesoporous titania films is solvent evaporation, which was first proposed by Ogawa [18,19]. Through the coating of precursor solutions, which include ethanol, inorganic species and surfactants, mesoporous titania films with various mesostructures, such as lamellar and 2D hexagonal mesostructures, can be prepared [20][21][22][23][24]. Yun et al reported the first example of anatase-crystallized mesoporous titania thin films with a 2D hexagonal mesoporous structure using the solvent evaporation method (figure 2(a)) [20].…”
Section: Mesoporous Titania Filmsmentioning
confidence: 99%
“…Titanium tetraisopropoxide (TTIP) is an alternative titanium source which results in a high reproducibility of the synthesis and is easy to handle. Wu et al found that the low aging temperature slowed down the hydrolysis and condensation reactions of TTIP that favored the formation of a highly ordered structure (figures 2(b) and (c)) [23]. Very recently, Nilsson et al developed a new direct synthesis methodology by using a microemulsion route for the preparation of mesoporous titania films with a 2D hexagonal mesostructure [24].…”
Section: Mesoporous Titania Filmsmentioning
confidence: 99%